2019
DOI: 10.1021/acscatal.9b03361
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition Promoted C–C Bond Cleavage in Rh-Mediated Cyclopropenone Activation: A DFT Study

Abstract: Computational characterization of the oxidation addition promoted in rhodium-catalyzed cyclopropenone activation and conversion via quinolyl-, pyridyl-, and nitrone-directed C–H activation is presented. Our theoretical studies found that a common catalytic cycle for these reactions starts with Rh­(III)-mediated concerted metalation–deprotonation or electrophilic deprotonation to afford the aryl-Rh­(III) intermediate. Oxidative addition of cyclopropenone to aryl-Rh­(III) then gives a cyclorhoda­(V)­butanone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…However, the pathway of ring-opening of cyclopropenones via C–C bond oxidative addition for accessing intermediate IV could not be excluded. 14 Finally, nucleophilic addition of the C–Rh bond to the ketimine followed by protonation gives rise to the desired spirolactam 3aa , and releases the active Rh( iii ) to continue the catalytic cycle.…”
mentioning
confidence: 99%
“…However, the pathway of ring-opening of cyclopropenones via C–C bond oxidative addition for accessing intermediate IV could not be excluded. 14 Finally, nucleophilic addition of the C–Rh bond to the ketimine followed by protonation gives rise to the desired spirolactam 3aa , and releases the active Rh( iii ) to continue the catalytic cycle.…”
mentioning
confidence: 99%
“…On the basis of the results presented above and previous reports, 37,48 plausible reaction mechanisms are presented in Scheme 7. Initially, the cyclopropenone is formed from difluorocyclopropene 2a in the presence of water.…”
Section: Organicmentioning
confidence: 99%
“…Mechanistic studies of the transition-metal-catalyzed ring-opening reactions of cyclopropenes have attracted substantial research interest. 5,10 For example, Xia et al 10 a conducted a DFT study to understand the mechanism of Rh( iii )-catalyzed C–H activation reactions of N -phenoxyacetamide and N -pivaloxybenzamide with cyclopropenes and indicated that the seven-membered rhodacycle from the migratory insertion of cyclopropene was crucial for both reactions. In addition, Lan and co-workers 10 f computationally studied the ring-opening of cyclopropenone in rhodium-catalyzed cyclopropenone conversion via quinolyl-, pyridyl-, and nitrone-directed C–H activation.…”
Section: Introductionmentioning
confidence: 99%